The Determinants of Household Consumption Expenditure in Nigeria - Olalere, Sunday Shina; Aladetanye, Tinuola Olawumi (Archives of Business Research, 2025)
Consumption expenditure is one of the important variables that have serious impact on overall economic performance of a nation. Therefore, this paper investigated the determinants of household consumption expenditure in Nigeria between 1981 and 2023. The study employed ARDL as an estimation technique and the findings of the study showed that, aggregate saving population size, population growth and level of inflation have serious influence on household consumption expenditure in Nigeria. Following these findings, the study therefore concluded that, aggregate savings, population size, population growth rate and rate of inflation greatly determine the household consumption expenditure in Nigeria. Based on this conclusion, the study made the following recommendations: policies that bring about reduction in the level of inflation in Nigeria should be formulated so as to enhance the consumption pattern of household at the same time, measures to enhance aggregate savings should put in place in the country since it contributes positively to the household consumption expenditure in Nigeria